Uma vila, várias famílias, muitas histórias (Almanack, 2025)
Resenha: METCALF, Alida C. Família e fronteira no Brasil colonial: Santana de Parnaíba, 1580-1822. Trad. Igor Machado de Lima e Ludmila de Souza Maia. São Paulo: Editora Unesp, 2024, 312p.